INSTITUTIONALIZATION AND FAMILY RELATIONSHIPS OF THE ELDERLY. - AGOSTINO, JOSEPH N. (ETC: A Review of General Semantics, 2023)
This paper provides an overview of the family as a viable and meaningful social support system for their elderly members. The paper examines the family relationships of the elderly and the impact of institutionalization on this relationship. Various alternatives to institutionalization are suggested.